Fluctuations, entropic quantifiers and classical-quantum transition - Pennini, Flavia (2014)
We show that a special entropic quantifier, called the statistical complexity, becomes maximal at the transition between super-Poisson and sub-Poisson regimes. This acquires important connotations given the fact that these regimes are usually associated with, respectively, classical and quantum processes.